A growth model for marketing evolution of multi-generation NAND flash memory. (14th December 2009) - Chiang, Su-Yun; Li, Yiming; Yu, Hsiao-Cheng
Marketing growth of information-technology products is continuously sustained by semiconductor non-volatile memories. Flash memory plays a crucial role for mass storage of portable electronic systems. In this work, we study the marketing dynamics of flash memory using a growth model. The model considering non-uniform influence, asymmetric diffusion, and heterogeneity of the population of potential adaptors is solved and optimised numerically. Comparison between simulated and realistic data for NAND flash memory from 128 Mb to 1 Gbit verifies the theoretical findings. The results of this study could be advanced for forecasting new technologies of flash memory.